UPAYA PENINGKATAN MOTIVASI DAN HASIL BELAJAR EKONOMI SISWA MENGGUNAKAN MEDIA KOMIK STRIP DI SMAN 2 BUNGO - mokhammad syaifuddin (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
This study aims to increase motivation and learning outcomes by using comic strip media. This research is a classroom action research (CAR). CAR is carried out in four stages, namely planning, implementation, observation and reflection. The subjects of this study were students of class XI IPS 1 SMAN 2 Bungo. Data collection techniques were carried out by observation and written tests. Based on the results of the study, the percentage of motivation in the first cycle was 58.53% in the sufficient category and increased in the second cycle by 81.96% in the high category. Based on the results of the evaluation in the first cycle, student learning completeness reached 62.22% with an average score of 72.8. In the second cycle, mastery learning increased to 84.44% with an average value of 84.06. Based on the results of the research above, it can be concluded that learning by using comic strip media can increase motivation and economic learning outcomes for students of class XI IPS SMAN 2 Bungo.